Dynamic Evaluation of Bridges: A Case Study of the Chenab Bridge in India - Jain, Anshul; Patel, Dr. Samir (Transportation Development Research, 2025)
The Chenab Bridge, located in Jammu and Kashmir, India, is the world’s highest railway arch bridge, standing 359 meters above the Chenab River with a main arch span of 467 meters. This paper presents a comprehensive dynamic evaluation of the bridge, focusing on its response to seismic, wind, and blast loads, which are critical given its location in a seismically active and windy Himalayan region. The study employs advanced numerical modeling, field measurements, and structural health monitoring (SHM) data to assess the bridge’s dynamic behavior. Finite element analysis (FEA) and wind tunnel tests are utilized to evaluate modal properties, dynamic amplification factors, and structural stability under extreme environmental conditions. Results indicate that the bridge’s steel arch design, coupled with its robust foundation system, effectively mitigates dynamic excitations, ensuring safety for rail operations at speeds up to 100 km/h. The paper highlights the importance of integrating real-time monitoring systems for long-term performance assessment and provides insights into the design and evaluation of high-altitude bridges in challenging terrains. This paper explores the Chenab Bridge, the world’s highest railway bridge in Jammu and Kashmir, India. It examines its innovative engineering, construction challenges, and socio-economic impact. The study highlights its role in regional connectivity and infrastructure development, offering insights into sustainable design and future railway expansion in challenging terrains.